2012
DOI: 10.1007/s12272-012-0318-1
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid-induced apoptosis in K562 cells involving upregulation of PTEN gene expression and inactivation of the PI3K/Akt pathway

Abstract: Ursolic acid (UA), a pentacyclic triterpenoid derived from a variety of medicinal plants, exhibits potent anticancer activity against many types of cancer cells. However, the anticancer mechanism of UA is not clearly understood. Suppression of phosphatase and a tensin homolog deleted on chromosome 10 (PTEN) gene expression leading to activation of the phosphatidylinositol-3-OH kinase (PI3K)/Akt pathway has been observed in many cancers including leukemia, making the PTEN gene and PI3K/Akt pathway a central tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Thus, Pten plays a critical role in distinguishing between leukemia stem cells and hematopoietic stem cells (Yilmaz et al, 2006). In a hematopoietic system, malignant tumors (e.g., leukemia, lymphoma, and myeloma), low expression, or deletion of the Pten gene or protein was related to poor patient prognosis (Wu et al, 2012). Furthermore, the Pten gene was inactivated by transcriptional silencing, posttranscriptional modification, and methylation (Xu et al, 2003;Yang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Pten plays a critical role in distinguishing between leukemia stem cells and hematopoietic stem cells (Yilmaz et al, 2006). In a hematopoietic system, malignant tumors (e.g., leukemia, lymphoma, and myeloma), low expression, or deletion of the Pten gene or protein was related to poor patient prognosis (Wu et al, 2012). Furthermore, the Pten gene was inactivated by transcriptional silencing, posttranscriptional modification, and methylation (Xu et al, 2003;Yang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the concrete mechanisms of its anticancer effects are poorly understood, several studies have found that UA can inhibit proliferation and induce apoptosis of many tumor cell lines. 2 UA-induced apoptosis occurs through multiple pathways such as the inhibition of DNA replication, 3 induction of Ca 2+ release, 4 activation of caspases 5,6 and c-Jun N-terminal kinase, 7,8 phosphorylation of glycogen synthase kinase 3-ÎČ, downregulation of antiapoptotic genes, 9 inhibition of cyclooxygenase-2 and inducible nitric oxide synthase, 10,11 suppression of matrixmetallopeptidase-9, 12 and the inhibition of protein tyrosine kinase, 13 phosphatidylinositol-3-kinase, 14 single transducer and activator of transcription 3, 15 adenosine 5â€Č-monophosphate-activated protein kinase, 16 and nuclear factor Îș-light-chain-enhancer of activated B cells 17 pathways. Furthermore, UA can inhibit the differentiation, angiogenesis, invasion, and metastasis of tumor cells as well as interfere with numerous enzymes such as those directly involved with DNA synthesis and repair.…”
Section: Introductionmentioning
confidence: 99%
“…This change was also associated with the downregulation of the anti-apoptotic gene Bcl-2 and melanoma progression in vitro [32]. Furthermore, Wu et al investigated leukemia (K562) cells and showed that UA is able to inhibit cellular growth by inducing apoptosis through the upregulation of PTEN gene expression and inhibiting the PI3K/ Akt/mTOR pathway [33]. A study by Leal et al demonstrated that UA initiates cell cycle arrest and apoptosis in pancreatic cancer (AsPC-1) cells with an upregulation in the levels of p53, p21 (waf1), and Noxa proteins [34].…”
Section: Therapeutic Roles Apoptosis and Cell Cycle Arrestmentioning
confidence: 96%